DUALISME KETENTUAN COST RECOVERY SEBAGAI DASAR PUNGUTAN NEGARA PADA INDUSTRI HULU MIGAS - Tambunan, Maria R.U.D.; Togatorop, Ginda (Veritas et Justitia, 2021)
This article traces and describes the changes made from time to time, to the calculation and determination of government share, as obtained from corporate revenues and tax deducted based on Production Sharing Contract, as used in the Indonesian natural gas and oil sector.   Qualitative data is gathered by performing a legal audit and literature review. The issue discussed here is the disagreement existing between the government and contractor regarding the calculation of recoverable cost (based on the Production Sharing Contract) and amount of corporate income tax imposed based on the prevailing tax law.  Based on the review of legal materials and literature, the recommended action is to harmonize these two different tax-revenue schemes.